A critique of service learning projects in management education: Pedagogical foundations, barriers, and guidelines - Kolenko, Thomas A. (Journal of business ethics, 1996)
This critique of nine service learning projects within schools of business is designed to encourage other educational institutions to add service learning requirements into business ethics and leadership courses. It champions the role of the faculty member teaching these courses while at the same time offering constructive analysis on pedagogy, a review of curriculum issues, identification of barriers to service learning, and guidelines for teaching service learning ventures. Challenges to all faculty involved in business ethics courses are made to better manage their courses and careers from a broader context outside of university settings.